Remodelação cardíaca induzida pelo tabagismo (tabaquismo) - Zornoff, Leonardo Antonio Mamede [UNESP]; Duarte, Daniella Resende [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP] (My University, 2007)
Previous studies accomplished by our group suggest that tobacco smoke exposure results in cardiac remodeling, with progressive ventricular dysfunction. However, the mechanisms involved in this process are not known. Therefore, our laboratory has been trying to identify the potentials responsible mechanisms for cardiac remodeling induced by tobacco. The blood pressure increase, the renin-angiotensin system and the oxidative stress can modulate this process. On the other hand, the activation of MMP-2 or MMP-9, as well as lipid peroxidation, don't seem to participate of the morphologic and functional alterations induced by tobacco smoke exposure.
Potential mechanisms of cardiac remodeling induced by tobacco
Keywords: Metalloproteinases; Oxidative stress; Renin-angiotensin system; Ventricular function; Ventricular remodeling; gelatinase A; gelatinase B; adrenergic system; blood pressure measurement; enzyme activation; heart ventricle function; heart ventricle remodeling; human; lipid peroxidation; morphology; oxidative stress; renin angiotensin aldosterone system; tobacco